Keragaman Genetik Beberapa Genotipe Jarak Pagar (Jatropha curcas L.) Berdaya Hasil Tinggi Berdasarkan Karakter Morfologi, Agronomi, dan Isozim - Dewi, Iswari S; Arisanti, Yusie; Purwoko, Bambang S.; Hariyadi, Hariyadi; Syukur, M. (Jurnal AgroBiogen, 2013)
The interest in using Jatropha curcas L. from thefamily Euphorbiaceae for the production of biofuel is rapidlygrowing. The research objective was to determine geneticvariation of several high yielding physic nuts based on theirmorphology, agronomy, and isozyme characters. Theresearch used Completely Randomized Design with threereplications. The treatment was consisted of 8 genotypes i.e.IP-1A, IP-1M, IP-2P, Lombok Timur, Lombok Tengah,Lombok Barat, Sumbawa, and Bima. Analysis of isozyme ofthe eight genotypes was also conducted according to 5enzyme systems, i.e. peroksidase, esterase, aspartataminotransferase, malat dehidrogenase, and alcoholdehidrogenase. Observation was done on qualitative andquantitative characters as well as banding pattern derivedisozymes.The results showed that genetic variation was lowwhen based on qualitative characters and isozyme (0-25%)but relatively high when based on selected quantitativecharacters analysis (17-81%). Analysis of combinedqualitative, quantitative, and isozyme characters still gavelow genetic variation (6-33%). Based on the quantitativecharacters at similarity coefficient of 46% the genotypes canbe devided into three clusters. Improved populationgenotypes, i.e. IP-1A, IP-1M, and IP-2P were placed in 3different clusters, while other genotypes from NTB areawere grouped in the same cluster. Therefore, selectionamong population of the same ecotype based on agronomiccharacters such as yield components, yield and oil contentwas suitable in Jatropha improvement, especially whengenetic variation was low. Furthermore, introduction,mutation and crossing are suggested to increase geneticvariation of current Jatropha collection.